2015
DOI: 10.4028/www.scientific.net/amr.1087.287
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aluminium Hydroxide (ATH) on the Mechanical Properties and Fire Resistivity of Palm-Based Fibreboard Prepared by Pre-Polymerization Method

Abstract: The aim of this study was to investigate the mechanical properties and fire resistivity of medium density fibreboards (MDF) made from renewable biomass namely empty fruit bunch fibre (EFB) and palm-based pre-PU as the binder. Aluminium hydroxide (ATH) was added in the mixture of EFB at size of 300 to 500 μm. The ratio of EFB to PU matrix was 35:65 with ATH at varying amount of 5, 10, and 15 wt% of the overall mass of the resin. The results showed that MDF-EFB has higher mechanical properties than MDF-EFB/ATH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…T onset10% for EGIM was 197°C, which was related to the expansion of the expandable graphite pulp fibers into a ''worm''-like char layer at a low temperature 160°C due to the redox reaction between the inserted H 2 SO 4 and the layered graphite [14]. For the SYIM sample, the Tmax 1 (254°C) could be due to the decomposition of aluminum hydroxide (ATH) at a temperature of 180°C [15]; and the catalytic dehydration of pulp fibers by the polyphosphates produced in the decomposition of ammonium polyphosphate (APP) [16]. As a result, the thermally stable char generated and that resulted in a higher Tmax 2 for SYIM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T onset10% for EGIM was 197°C, which was related to the expansion of the expandable graphite pulp fibers into a ''worm''-like char layer at a low temperature 160°C due to the redox reaction between the inserted H 2 SO 4 and the layered graphite [14]. For the SYIM sample, the Tmax 1 (254°C) could be due to the decomposition of aluminum hydroxide (ATH) at a temperature of 180°C [15]; and the catalytic dehydration of pulp fibers by the polyphosphates produced in the decomposition of ammonium polyphosphate (APP) [16]. As a result, the thermally stable char generated and that resulted in a higher Tmax 2 for SYIM.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to model the material behavior when the material is exposed to a fire due to the complex combination of fluid dynamics, combustion, heat and mass transfer, and kinetics [13]. Many studies on the contributions of fire retardant have concluded that a fire retardant can catalyze the cellulose degradation and improve the generation of char that reduces the heat and mass transfer [14][15][16]. The thermal stability, decomposition rate, char-forming rate, and char yield of the thermal insulating materials also affect the fire retardancy [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For the synergetic fire retardant + MFC-coated sample, the residue formed a shrunken char and could not maintain its original shape. This was due to stress changes during the catalytic dehydration of cellulosic fibers by polyphosphates produced during ammonium polyphosphate (APP) decomposition (Seefeldt et al 2012), water release and formation of Al 2 O 3 ( Figure 8f) from aluminum hydroxide (ATH) decomposition at 180°C (Musbah Redwan et al 2015), and the evolution of diluted gases, such as NH 3 (Statheropoulos and Kyriakou 2000). Additionally, the generation of thermally stable char resulted in a higher T max in the late stage, as evidenced by thermal gravimet- ric analysis (Figure 3).…”
Section: Cone Calorimetrymentioning
confidence: 99%
“…The application of minerals in wood and wood‐based materials has attracted increased attention 1‐6 . Among the various advantages of the application of mineral additives in wood‐based materials, such as the potential cost reduction, the applications as a fire retardant (FR) is considered one of the most promising fields.…”
Section: Introductionmentioning
confidence: 99%